PRAME immunohistochemistry in soft tissue tumors and mimics: a study of 350 cases highlighting its imperfect specificity but potentially useful diagnostic applications - Cammareri, Chloé; Beltzung, Fanny; Michal, Michael; Vanhersecke, Lucile; Coindre, Jean-Michel; Velasco, Valérie; Le Loarer, François; Vergier, Béatrice; Perret, Raul (Virchows Archiv : an international journal of pathology, 2023)
Preferentially expressed antigen in melanoma (PRAME) immunohistochemistry is currently used in pathology for the assessment of melanocytic neoplasms; however, knowledge of its expression patterns in soft tissue tumors is limited. PRAME immunohistochemistry (clone QR005) was assessed on whole tissue sections of 350 soft-tissue tumors and mimics (> 50 histotypes). PRAME immunoreactivity was evaluated as follows: 0 “negative” (0% positive cells); 1+ (1–25% positive cells); 2+ (26–50% positive cells); 3+ (51–75% positive cells), and 4+ “diffuse” (> 75% positive cells). PRAME was expressed in 111 lesions (0 benign, 6 intermediate malignancy, and 105 malignant), including fibrosarcomatous dermatofibrosarcoma protuberans (2/4, 0 diffuse), NTRK -rearranged spindle cell neoplasm (2/4, 0 diffuse), atypical fibroxanthoma (1/7, 0 diffuse), Kaposi sarcoma (1/5, 0 diffuse), myxoid liposarcoma (11/11, 9 diffuse), synovial sarcoma (11/11, 6 diffuse), intimal sarcoma (7/7, 5 diffuse), biphenotypic sinonasal sarcoma (3/3, 1 diffuse), angiosarcoma (10/15, 6 diffuse), malignant peripheral nerve sheath tumor (9/12, 4 diffuse), pleomorphic rhabdomyosarcoma (2/3, 2 diffuse), alveolar rhabdomyosarcoma (2/6, 0 diffuse), embryonal rhabdomyosarcoma (7/7, 4 diffuse), undifferentiated pleomorphic sarcoma (2/12, 1 diffuse), leiomyosarcoma (2/15, 1 diffuse), clear cell sarcoma of soft tissue (1/10, 0 diffuse), low-grade fibromyxoid sarcoma (1/5, 0 diffuse), Ewing sarcoma (2/10, 1 diffuse), CIC -rearranged sarcoma (8/8, 4 diffuse), BCOR -sarcoma (2/5, 1 diffuse), melanoma (20/20, 14 diffuse), and thoracic SMARCA4-deficient undifferentiated tumor (5/5, all diffuse). All tested cases of spindle cell lipoma, dedifferentiated/pleomorphic liposarcoma, dermatofibrosarcoma protuberans, solitary fibrous tumor, inflammatory myofibroblastic tumor, myxoinflammatory fibroblastic sarcoma, nodular fasciitis, myxofibrosarcoma, epithelioid hemangioendothelioma, atypical vascular lesion, hemangioma, lymphangioma, vascular malformation, papillary endothelial hyperplasia, GIST, gastrointestinal clear-cell sarcoma, malignant melanotic nerve sheath tumor, neurofibroma, schwannoma, granular cell tumor, alveolar soft part sarcoma, epithelioid sarcoma, extraskeletal myxoid chondrosarcoma, myoepithelioma, ossifying fibromyxoid tumor, angiomatoid fibrous histiocytoma, PEComa, dermatofibroma, pleomorphic dermal sarcoma, and chordoma were negative. PRAME shows imperfect specificity in soft-tissue pathology but may serve as a diagnostic adjunct in selected differential diagnoses that show contrasting expression patterns.